Research on Arc Extinguishing Characteristics of Single-Phase Grounding Fault in Distribution Network - Yan Li; Jianyuan Xu; Peng Wang; Guanhua Li (Energies)
The development of a single-phase grounding fault arc is influenced by various environmental factors, which can result in the rapid extinction and reignition of the arc. This phenomenon can lead to accidents, such as resonant overvoltage. Current grounding arc models inadequately account for the effects of grounding current, arc length, environmental wind speed, and other variables on the characteristics of the arc. In response to this issue, this article establishes a three-dimensional single-phase grounding arc mathematical model grounded in magnetohydrodynamics. It simulates and analyzes the effects of arc length and environmental wind speed on both arc ignition and extinguishing. Furthermore, an artificial single-phase grounding test platform is constructed within the actual distribution network to validate the accuracy of the simulation model. Research has demonstrated that, under identical operating conditions for both simulation and experimentation, the error range between the simulated arc voltage and the measured data is within 8%. The three-dimensional single-phase grounding arc mathematical model effectively describes the dynamic development process of the grounding arc. At a gap of 12 cm, under windless conditions and with a grounding current of 40.0 A, the temperature of the arc column at the peak of the current reaches 2600 K, while the conductivity decreases to 2.1 × 10−4 S/m, resulting in the inability of the arc to sustain a burning state. At a gap of 2 cm and a wind speed of 7 m/s, the temperature of the arc column at the peak of the current reaches 2900 K, the conductivity drops to 4.3 × 10−3 S/m, leading to the extinction of the arc.